2016
DOI: 10.1097/nmd.0000000000000531
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Recognition of Depressive Disorder in Three Medical Outpatient Departments of General Hospitals in Beijing, China

Abstract: This purpose of this study was to explore the prevalence and recognition of depressive disorders in cardiology, gastroenterology, and neurology outpatient departments of general hospitals. Patients screened with a Hospital Anxiety and Depression Scale score of 8 or higher were interviewed by psychiatrists using Mini-International Neuropsychiatric Interview (MINI). Prevalence of depressive disorders within the cohort was determined, sociodemographic data were analyzed for correlations to a depression diagnosis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…In the present study, 2012 accounted for 46.2% of the total number of outpatients in the 3 years covered (2010-2012), and the number of consultations for mental illness reached 44.3%, suggesting that the workload on psychiatric departments in China is increasing 18 . Nevertheless, a previous study in China showed that physicians in non-psychiatric departments only recognized about 27% of patients with depressive disorders 19 .…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, 2012 accounted for 46.2% of the total number of outpatients in the 3 years covered (2010-2012), and the number of consultations for mental illness reached 44.3%, suggesting that the workload on psychiatric departments in China is increasing 18 . Nevertheless, a previous study in China showed that physicians in non-psychiatric departments only recognized about 27% of patients with depressive disorders 19 .…”
Section: Discussionmentioning
confidence: 99%